2013
DOI: 10.1681/asn.2012020133
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes Are Nonhematopoietic Professional Antigen-Presenting Cells

Abstract: Podocytes are essential to the structure and function of the glomerular filtration barrier; however, they also exhibit increased expression of MHC class II molecules under inflammatory conditions, and they remove Ig and immune complexes from the glomerular basement membrane (GBM). This finding suggests that podocytes may act as antigen-presenting cells, taking up and processing antigens to initiate specific T cell responses, similar to professional hematopoietic cells such as dendritic cells or macrophages. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 40 publications
(44 reference statements)
6
122
0
Order By: Relevance
“…Other resident glomerular cells may have more significant roles in the activation of T cells around the glomeruli. Recent studies have indicated that podocytes from parietal epithelial cells were the predominant cellular components of crescents (Appel et al, 2009); these podocytes function as local professional antigen-presenting cells in the kidney (Goldwich et al, 2013) and may destroy its structure (Li et al, 2015). Further studies are required to determine the mechanisms of interaction between T cells and podocytes to elucidate the activation of CD4 + cells in the kidney in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Other resident glomerular cells may have more significant roles in the activation of T cells around the glomeruli. Recent studies have indicated that podocytes from parietal epithelial cells were the predominant cellular components of crescents (Appel et al, 2009); these podocytes function as local professional antigen-presenting cells in the kidney (Goldwich et al, 2013) and may destroy its structure (Li et al, 2015). Further studies are required to determine the mechanisms of interaction between T cells and podocytes to elucidate the activation of CD4 + cells in the kidney in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [21] further showed that murine podocytes expressed NLRP3, ASC and caspase-1, and in mice with hyperhomocysteinemia, IL-1β increased in the glomeruli. Given that podocytes act like dendritic cells and infiltrating macrophages [22], their ability to participate in inflammation is convincing. Whether these controversial results are the result of different stimuli remains unknown.…”
Section: Introduction Of the Inflammasomementioning
confidence: 99%
“…Podocytes express MHC class I and class II molecules, and this increases under inflammatory conditions. 11,12 Furthermore, podocytes can serve as antigen-presenting cells, and deleting MHC class II exclusively on podocytes markedly attenuates the severity of GN in a mouse model of anti-GBM nephritis. 12 Yang et al 9 did not compare glomerulitis in their cases of early versus late TG, and they observed acute ABMR only infrequently before the development of early or late TG, although diagnosis was based on an older version of the Banff classification that did not recognize C4d-negative ABMR.…”
mentioning
confidence: 99%
“…11,12 Furthermore, podocytes can serve as antigen-presenting cells, and deleting MHC class II exclusively on podocytes markedly attenuates the severity of GN in a mouse model of anti-GBM nephritis. 12 Yang et al 9 did not compare glomerulitis in their cases of early versus late TG, and they observed acute ABMR only infrequently before the development of early or late TG, although diagnosis was based on an older version of the Banff classification that did not recognize C4d-negative ABMR. However, 5 of 8 cases of early TG were associated with a history of TCMR (Banff 1A or above) compared with only 2 of 17 cases of late TG, suggesting that an inflammatory environment may have been present, at least transiently, in the majority of kidneys developing early TG, 6 of 8 of which were also exposed to DSAs.…”
mentioning
confidence: 99%